2011
DOI: 10.1021/am2010459
|View full text |Cite
|
Sign up to set email alerts
|

Large Dielectric Constant and High Thermal Conductivity in Poly(vinylidene fluoride)/Barium Titanate/Silicon Carbide Three-Phase Nanocomposites

Abstract: Dielectric polymer composites with high dielectric constants and high thermal conductivity have many potential applications in modern electronic and electrical industry. In this study, three-phase composites comprising poly(vinylidene fluoride) (PVDF), barium titanate (BT) nanoparticles, and β-silicon carbide (β-SiC) whiskers were prepared. The superiority of this method is that, when compared with the two-phase PVDF/BT composites, three-phase composites not only show significantly increased dielectric constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
230
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(239 citation statements)
references
References 47 publications
9
230
0
Order By: Relevance
“…Compared with the reported ceramic/PVDF composites and conductive metal Zn/PVDF [5,7,9,20,21], the dielectric constant of PVDF/V 2 O 5 composites is significantly higher at low filler content. Furthermore, it can be obviously found that our V 2 O 5 /PVDF composites possess higher dielectric constant than other semiconductor/polymers nanocomposites, such as ZnO/PVDF, TiO 2 /polystyrene, and ZnO/ polyethylene reported at a low filler content [10,22,23].…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Compared with the reported ceramic/PVDF composites and conductive metal Zn/PVDF [5,7,9,20,21], the dielectric constant of PVDF/V 2 O 5 composites is significantly higher at low filler content. Furthermore, it can be obviously found that our V 2 O 5 /PVDF composites possess higher dielectric constant than other semiconductor/polymers nanocomposites, such as ZnO/PVDF, TiO 2 /polystyrene, and ZnO/ polyethylene reported at a low filler content [10,22,23].…”
mentioning
confidence: 72%
“…Thus, it is a key issue to enhance dielectric permittivity of polymers while retaining other excellent performances. One versatile route is to disperse a high dielectric constant ceramic powder [5,6] into the polymer matrix [7][8][9], which can combine excellent dielectric behavior of fillers with superior processing property and chemical stability from the polymers. However, the excellent dielectric properties of such composites need high particle concentration (over 60 vol%), which can lead to the degradation of mechanical properties and processability of the polymers.…”
mentioning
confidence: 99%
“…Our results are close enough to the ideal region by demonstrating the dielectric constant of $303 with a loss of $0.08. The composite cases with higher 3 r than our value are based on thermally cured bulk samples heat-treated at 160 to 200 C. 15,17,34 The yellow highlighted region in the le bottom region of Fig. 8 corresponds to the BaTiO 3 -based composite examples not containing percolative metal particles, 10,35-37 which can be characterized with low dielectric constant with acceptable dielectric loss.…”
Section: Effects Of Dispersed Ag Nanoparticles In Nanocomposite Lmsmentioning
confidence: 74%
“…A series of related studies has been proposed to solve this problem [14][15][16][17]. A general method is to use high k materials as fillers to significantly improve the dielectric properties of polymers [18][19][20][21][22][23]. It is well known that polyvinylidene fluoride (PVDF) has a relatively high dielectric constant (10)(11)(12)(13)(14) [24,25] which can be used as a high dielectric filler to improve the dielectric constant of PI.…”
Section: Introductionmentioning
confidence: 99%